2016
DOI: 10.15171/jlms.2016.09
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Neodymium-Doped Yttrium Aluminium Garnet (Nd:YAG) Laser Irradiation on Bone Metabolism During Tooth Movement

Abstract: IntroductionOrthodontic treatment involves moving tooth by force application and it requires a period of time. Prolonged orthodontic treatment can be a threat to oral hygiene and a source of trauma to oral tissue. Shortening the treatment time becomes one of the challenges for orthodontists. Several approaches have been described in the literature. Köle et al 1 reported that corticotomy accelerated experimental tooth movement in rats. Also Tuncay et al 2 and Young et al 3 reported that fiberotomy could achieve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…In previous experiments, the irradiation effect of the Nd: YAG laser during orthodontic tooth movement was investigated using rats and it was proved that there was a change in bone metabolism and tooth movement. 18 In addition, in a previous study from the authors, a wound healing test was performed by irradiating osteoblast-like cells with a diode laser and confirmed that the cells proliferated. 12 There are many researches using the Nd: YAG laser in in vitro experiments, but there is no cell experiment model considering tooth movement.…”
Section: Introductionmentioning
confidence: 79%
“…In previous experiments, the irradiation effect of the Nd: YAG laser during orthodontic tooth movement was investigated using rats and it was proved that there was a change in bone metabolism and tooth movement. 18 In addition, in a previous study from the authors, a wound healing test was performed by irradiating osteoblast-like cells with a diode laser and confirmed that the cells proliferated. 12 There are many researches using the Nd: YAG laser in in vitro experiments, but there is no cell experiment model considering tooth movement.…”
Section: Introductionmentioning
confidence: 79%
“…Fujita et al (22) indicated that the amount of tooth movement on day 7 was significantly greater in a laserirradiation group than in a non-irradiation group. Another study has also shown that the amount of tooth movement on day 7 was significantly greater in an irradiation group than in a control group (15). However, there was no difference in the amount of tooth movement on days 14, 21, and 28.…”
Section: Discussionmentioning
confidence: 91%
“…ment of teeth using Nd:YAG laser has been demonstrated so far (15). However, the degree of acceleration was very small.…”
Section: Molecular Biological and Histological Effects Of Er:yag Lasementioning
confidence: 98%
“…Administration of platelet-rich plasma (4), adiponectin (5), bisphosphonates (6), methylphenidate (7), dihydroxyvitamin D3 (8), parathyroid hormone (9), prostaglandin E2 (PGE2) (10), osteocalcin (11), icariin (12), and vitamin C (2) have been employed to increase rapidity and quality of orthodontic tooth movement. Investigators tested non-invasive techniques that are well accepted by patients including low level laser therapy (13)(14)(15) and low intensity pulsed ultrasound (16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%